THE IMPACT OF MOTHER TONGUE ON GRAMMAR AND SENTENCE STRUCTURE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the influence of mother tongue on grammar and sentence structure in second language acquisition. It highlights how native language structures can shape learners' understanding and usage of a new language, leading to both positive and negative outcomes. The findings suggest that awareness of these influences can enhance teaching methodologies.